2002
DOI: 10.1034/j.1600-0676.2002.00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid dysbalance in liver failure is favourably influenced by recirculating albumin dialysis (MARS)

Abstract: MARS enables an elevation of a pathologically decreased Fischer's Index as well as a reduction of systemic tryptophan levels in patients with liver failure. The effects of MARS on plasma amino acid dysbalance may contribute to an improvement of hepatic encephalopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The fact that these patients were, therefore, in better clinical condition prior to LTX might contribute to the high overall survival of transplanted patients. The favorable effect of MARS treatment on laboratory parameters, as we observed, has also been reported in many small, uncontrolled studies [26,27,[37][38][39][40][41][42][43][44] . However, the improvement in laboratory values alone might be only temporary and does not necessarily predict a favorable outcome.…”
Section: Discussionsupporting
confidence: 65%
“…The fact that these patients were, therefore, in better clinical condition prior to LTX might contribute to the high overall survival of transplanted patients. The favorable effect of MARS treatment on laboratory parameters, as we observed, has also been reported in many small, uncontrolled studies [26,27,[37][38][39][40][41][42][43][44] . However, the improvement in laboratory values alone might be only temporary and does not necessarily predict a favorable outcome.…”
Section: Discussionsupporting
confidence: 65%
“…In contrast, Loock et al. reported a statistically significant decrease of BCAAs, interestingly without noticing a removal of them by both adsorbers used in MARS (6). Tryptophan is another important amino acid that is related to hepatic encephalopathy.…”
Section: Discussionmentioning
confidence: 97%
“…To date, two studies have reported data on the effect of MARS extracorporeal therapy on amino acids. Both articles described an improvement of the amino acid dysbalance (5,6). Schmidt et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MARS was used continuously until LTx. Median time (range) on MARS treatment prior to LTx in groups I-III was 7 days (2-26), 6 days (1-17), and 5 days (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), and the median time on the waiting list was 5 days (1-11), 3 days (0-13), and 1 day (0-12), respectively. The HE grade prior to and after MARS was similar in all groups.…”
mentioning
confidence: 99%